Characterization of hepatitis virus co‐infections in a cohort of immigrants living in southern Italy. Issue 3 (23rd March 2023) - Pisaturo, Mariantonietta; Alessio, Loredana; Starace, Mario; Macera, Margherita; Occhiello, Laura; Cordua, Emanuele; Capuano, Salvatore; Onorato, Lorenzo; Scotto, Gaetano; Di Caprio, Giovanni; Calò, Federica; Monari, Caterina; et al.
Abstract: To characterize viral hepatitis co‐infections in a cohort of immigrants living in southern Italy. In a prospective multicenter study, all undocumented immigrants and low‐income refugees consecutively evaluated for a clinical consultation at one of the five first‐level clinical centers in southern Italy from January 2012 to February 2020 were enrolled. All subjects included in the study were screened for hepatitis B surface antigen (HBsAg), anti‐hepatitis C virus (HCV) and anti‐HIV; the HBsAg‐positive were screened also for anti‐delta. Of the 2923 subjects enrolled, 257 (8%) were HBsAg‐positive alone (Control group B), 85 (2.9%) only anti‐HCV‐positive (Control group C), 16 (0.5%) HBsAg/anti‐HCV‐positive (Case group BC), and 8 (0.2%) HBsAg/anti‐HDV‐positive (Case group BD). Moreover, 57 (1.9%) subjects were anti‐HIV‐positive. HBV‐DNA positivity was found less frequently in the 16 subjects in Case group BC (43%) and in the 8 in Case group BD (12.5%) than in the 257 in Control group B (76%; p  = 0.03 and 0.0000, respectively). Similarly, HCV‐RNA positivity was more frequent in Case group BC than in Control group C (75% vs. 44.7% p  = 0.02). The subjects in Group BC had a lower prevalence of asymptomatic liver disease (12.5%) than Control group B (62.2%, p  = 0.0001) and Control group C (62.3%, p  = 0.0002). Conversely, liver cirrhosis was more frequently identified in Case group BC (25%) than in Control groups B and C (3.11% and 2.35%, p  = 0.0000 and 0.0004, respectively). The present study contributes to the characterization of hepatitis virus co‐infections in the immigrant population.